Gender effect on the pharmacokinetics of thymoquinone: Preclinical investigation and in silico modeling in male and female rats - Ajaz Ahmad; Saeed Alqahtani; Basit Latief Jan; Mohammad Raish; Abdullah K. Rabba; Khalid M. Alkharfy (Elsevier, 2020)
Thymoquinone is the most biologically active constituent of Nigella sativa (black seed). A monoterpene compound chemically known as 2-methyl-5-isopropyl-1, 4-quinone. In this study, the gender-dependent pharmacokinetic behavior of thymoquinone in rats was investigated. Thymoquinone was administered orally (20 mg/kg) and intravenously (5 mg/kg) to male and female rats and blood samples were collected at specific time points. Plasma concentration-time curves were plotted and pharmacokinetic parameters were determined using the non-compartmental analysis. In addition, simulations of steady state concentrations of thymoquinone in male and female rats were performed using GastroPlus PK software. After oral administration, the maximum plasma concentration (Cmax) of thymoquinone was 4.52 ± 0.092 μg/ml in male rats and 5.22 ± 0.154 μg/ml in female rats (p = 0.002). Similarly, after intravenous administration, the Cmax was 8.36 ± 0.132 μg/ml in males and 9.51 ± 0.158 μg/ml in females (p = 0.550). The area under the plasma concentration-time curve (AUC)0-∞ following oral dosing was 47.38 ± 0.821 μg/ml·h in females and 43.63 ± 0.953 μg/ml·h in males (p = 0.014). Pharmacokinetics and plasma concentration vs. time profiles for multiple oral doses of thymoquinone in rats were predicted using a simulation model to compare the simulation results with the experimental plasma pharmacokinetic data. The differences observed in thymoquinone pharmacokinetics between male and female rats after a single dose were not evident for the simulated steady-state parameters. The findings suggest that the gender difference does not seem to play a significant role in thymoquinone disposition at steady state. Keywords: Thymoquinone, Male and female rats, Plasma, Pharmacokinetics, GastroPlus PK simulations